Categorical and dimensional approaches to negative symptoms of schizophrenia: Focus on long-term stability and functional outcome - Galderisi, Silvana; Bucci, Paola; Mucci, Armida; Kirkpatrick, Brian; Pini, Stefano; Rossi, Alessandro; Vita, Antonio; Maj, Mario (Schizophrenia research, 2013)
Negative symptoms of schizophrenia represent a heterogeneous psychopathological domain. Both categorical and dimensional approaches have been proposed to reduce negative symptoms heterogeneity. In the present 5-year follow-up study, long-term stability and impact on outcome of different aspects of negative symptoms were investigated. Following a categorical approach, long-term stability and outcome of deficit schizophrenia (DS), in comparison with nondeficit schizophrenia (NDS), were assessed. Following a dimensional approach, the factor structure and stability of broadly defined negative symptoms and the ability of the identified factors to predict functional outcome were investigated. DS and NDS subjects included in a previous study were invited to participate. Fifty-one out of 58 patients previously diagnosed as DS and 44 out of 54 NDS patients were included in the present study. The DS/NDS categorization was confirmed in 82.4% of DS and 79.6% of NDS subjects. At follow-up, DS patients showed more severe negative symptoms and greater social dysfunction than NDS ones. Schedule for the Deficit Syndrome (SDS) severity scores loaded on two factors: “Poor Emotional Expression” and “Avolition” and the factor structure was stable after 5years. Avolition was associated to social outcome measures and Poor Emotional Expression to functioning in household activities. Psychosocial outcome was predicted by SDS factors reflecting the severity of broadly defined negative symptoms, but not by the DS/NDS categorization. This might lend support to the recent shift of research focus from the categorical approach focusing on the presence of primary and enduring negative symptoms to the investigation of key domains of broadly defined negative symptoms.